Nanotechnology in Advancing Chimeric Antigen Receptor T Cell Therapy for Cancer Treatment - Xuejia Kang; Nur Mita; Lang Zhou; Siqi Wu; Zongliang Yue; R. Jayachandra Babu; Pengyu Chen (MDPI AG, 2024)
Chimeric antigen receptor (CAR) T cell therapy has emerged as a groundbreaking treatment for hematological cancers, yet it faces significant hurdles, particularly regarding its efficacy in solid tumors and concerning associated adverse effects. This review provides a comprehensive analysis of the advancements and ongoing challenges in CAR-T therapy. We highlight the transformative potential of nanotechnology in enhancing CAR-T therapy by improving targeting precision, modulating the immune-suppressive tumor microenvironment, and overcoming physical barriers. Nanotechnology facilitates efficient CAR gene delivery into T cells, boosting transfection efficiency and potentially reducing therapy costs. Moreover, nanotechnology offers innovative solutions to mitigate cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS). Cutting-edge nanotechnology platforms for real-time monitoring of CAR-T cell activity and cytokine release are also discussed. By integrating these advancements, we aim to provide valuable insights and pave the way for the next generation of CAR-T cell therapies to overcome current limitations and enhance therapeutic outcomes.